2(1-(-8x-9))=128x+146

Simple and best practice solution for 2(1-(-8x-9))=128x+146 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(1-(-8x-9))=128x+146 equation:


Simplifying
2(1 + -1(-8x + -9)) = 128x + 146

Reorder the terms:
2(1 + -1(-9 + -8x)) = 128x + 146
2(1 + (-9 * -1 + -8x * -1)) = 128x + 146
2(1 + (9 + 8x)) = 128x + 146

Combine like terms: 1 + 9 = 10
2(10 + 8x) = 128x + 146
(10 * 2 + 8x * 2) = 128x + 146
(20 + 16x) = 128x + 146

Reorder the terms:
20 + 16x = 146 + 128x

Solving
20 + 16x = 146 + 128x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-128x' to each side of the equation.
20 + 16x + -128x = 146 + 128x + -128x

Combine like terms: 16x + -128x = -112x
20 + -112x = 146 + 128x + -128x

Combine like terms: 128x + -128x = 0
20 + -112x = 146 + 0
20 + -112x = 146

Add '-20' to each side of the equation.
20 + -20 + -112x = 146 + -20

Combine like terms: 20 + -20 = 0
0 + -112x = 146 + -20
-112x = 146 + -20

Combine like terms: 146 + -20 = 126
-112x = 126

Divide each side by '-112'.
x = -1.125

Simplifying
x = -1.125

See similar equations:

| (3-7/3+4/3)/(1/2-2-5/5)*3/8 | | -17x=g-204 | | 2+9(-7c+2)= | | 1+27/8 | | 3+4=5+x | | 4/9+8/9= | | 18h=3(6h+4)-12 | | 2/3+4/5x=1/3x+2 | | 35+x=45 | | 3/5+x=8/5 | | 1/2y+4=-2/3y+1/2 | | -4=2x+3(-2-8) | | 7x-51-3x=21 | | 4(x+2)+28=6x-2(x-6) | | 2(1-3k)-3k=-5k+7(k-6) | | 11x-156-2x=60 | | (9t/20)-(t/4)=t | | 5+7(-2y-3)= | | 1/5x+1/2=4 | | (x+y)*10=100 | | (9t/20-t/4)=t | | 5x+3=24-2x | | x/3+3x/4=26 | | 9t/20-t/4=t | | -(3k-4)=7-(k-3) | | x+(-16)=44 | | (2+4.8)3=(2n)+(4.8n) | | 24(x-6)=-56x+8 | | 6x-12=600 | | -3(2+4m)=10-8m | | 5p-12=9p+8 | | -4(v+3)=3v-33 |

Equations solver categories